2012
DOI: 10.1021/jp211947y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Mixed Diindenoperylene–Perfluoropentacene Thin Films

Abstract: Mixed films of perfluorinated pentacene and diindenoperylene are studied for their structural and optical properties on SiO 2 and glass substrates. Grazing incidence Xray diffraction shows that the compounds mix on the molecular level. Two structures are identified. Their out-ofplane lattice spacing is determined by X-ray reflectivity, and their growth morphology is characterized using atomic force microscopy. It is found that one structure consists of molecules in a standing-up and the other in a lying-down o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 55 publications
5
54
1
Order By: Relevance
“…32. For the equimolar mixture no Bragg-peaks at q || -positions corresponding to the pure films were observed, but Bragg-peaks significantly different in q || -position indicate the formation of a mixed crystal phase.…”
Section: A Post Growth Xrr-measurementsmentioning
confidence: 84%
See 3 more Smart Citations
“…32. For the equimolar mixture no Bragg-peaks at q || -positions corresponding to the pure films were observed, but Bragg-peaks significantly different in q || -position indicate the formation of a mixed crystal phase.…”
Section: A Post Growth Xrr-measurementsmentioning
confidence: 84%
“…32. There, also the shift of the first observable peak in 2, xy (E) of the equimolar PFP:DIP mixture with film thickness was discussed.…”
Section: Thickness Dependence Of the Imaginary Part Of The Dielectricmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, it was shown that a molecular complex is also formed in mixed PFP:DIP thin films. [123] Importantly, upon mixing PEN and PFP, in optical absorption spectra a new transition arises at 1.6 eV (Figure 7 b), which is not present in either of the spectra of the pure materials and indeed also below both of the respective gaps. [121] Detailed analysis shows that the absorption spectrum of PEN:PFP cannot be explained by a superposition of the spectra of the pure substances.…”
Section: Phase Separation In A:b Systemsmentioning
confidence: 96%